Jual Beli Barang Menggunakan Coin Flip: Perspektif Hukum positif di Indonesia - Adam Malik Siregar; Aditya Prastian Supriyadi; Mustafa lutfi (Journal of Islamic Business Law, 2026)
The phenomenon of buying and selling using the coin flip agreement system, which has gone viral on social media, has raised legal issues in Indonesia. This system uses coin tossing to determine the price of goods, creating uncertainty that has the potential to harm one of the parties. This study analyzes the legality of the coin flip practice based on Indonesian positive law using a normative juridical method. The results of the study indicate that although coin flip transactions meet the requirements for a valid agreement under Article 1320 of the Civil Code, this practice distorts the principles of fair and transparent pricing as stipulated in Law No. 8 of 1999 on Consumer Protection. This transaction also contains speculative elements resembling gambling, but Article 303 of the Criminal Code does not explicitly regulate sales and purchases involving elements of chance. From an Islamic law perspective, this practice involves gharar, which contradicts Fatwa DSN-MUI No. 112/2017. The study concludes that there is a legal vacuum in regulating online transactions that involve speculative elements, therefore stricter regulations are needed to ensure legal certainty and consumer protection.